Association of financial literacy and food insecurity among undergraduate students in USM Health Campus - Jie, Wong Yong (Universiti Sains Malaysia, 2024)
The increasing prevalence of food insecurity among university students is a critical issue. A lack of food and money management skills, such as the inability to plan a budget and manage expenses due to inadequate financial literacy, might affect one's level of food security. This study investigates the association between financial literacy and food insecurity among undergraduate students at the USM Health Campus. A cross-sectional study design was employed, involving a sample size of 169 students recruited through stratified random sampling. Data were collected using a structured questionnaire that assessed demographic and socioeconomic characteristics, food security status, and financial literacy. The data were analyzed using Pearson’s Chi-square test or Fisher Exact test. Results indicated that 49.8% of students experienced food insecurity, with significant differences observed based on ethnicity, mother’s education level, and household income. The study found that 21.9% of university students have a low level of financial literacy, 37.8% have a medium level, and 40.2% possess a high level of financial literacy. However, there is no significant association between financial literacy and food security status among university students. These findings suggest that while improving financial literacy is important, it may not be sufficient on its own to address food insecurity among students. Further research is needed to explore other contributing factors and develop comprehensive strategies to mitigate food insecurity in this population.